Desarrollo y aplicación de un modelo de madurez en transformación digital para pequeñas y medianas empresas constructoras (2020)
The purpose of this work is to analyze the impact that lack of digitalization has over the enterprises of middle and little size, to establish the most clear route to give the first step to digitalization. For this, it is important to make an analysis of the construction sector and the way that enterprises has created value over the years. This way, this paper seek to find the convergence points in which actions can be prioritized to implement digital transformation in construction companies and demonstrate the immediate need to apply these methodologies holistically not only in organization processes but also over stakeholders.